Integrating Blockchain in Scheduling: A Comprehensive Review of Current Trends and Future Directions - Bahroun, Zied; Shamayleh, Abdulrahim; Tanash, Moayad; Rawshdeh, Mustafa; Alastal, Haya (Decision Making: Applications in Management and Engineering, 2024)
This review paper offers a comprehensive exploration of blockchain technology’s integration in scheduling activities across various industries. It systematically gathered and analyzed literature, identifying 133 relevant documents through rigorous screening from 2017 till 2023. The bibliometric analysis, including co-authorship and co-occurrence maps, revealed key trends, influential authors, and emerging research areas. Content analysis focused on blockchain applications in service optimization, system and resource planning, management, project and production planning, energy optimization, and security enhancement. The research acknowledged significant advancements in these areas, particularly in terms of improved efficiency, transparency, and security. The findings underscore the potential of blockchain in revolutionizing scheduling and management processes across different sectors, highlighting the need for further exploration of its applications and implications in various professional contexts. The paper aims to bridge the gap in the literature by presenting a holistic view of blockchain’s role in advancing scheduling methods, driving innovation, and fostering more robust, efficient, and transparent scheduling systems across industries.